A Framework to Optimize Efficiency of New Hire Onboarding Process - Wilkhoo, Manmeet Kaur (Digital Repository of Theses, 2025)
Title: Enhancing Efficiency of New Hire Onboarding Process: A comprehensive analysis for optimizing efficiency of onboarding process is a critical element for integrating new employees into an organizations. This research aims to explore and analyse the framework to ensure employees become productive and engaged within organization, shedding light on the factors that influence onboarding process outcomes and proposing strategies for improvement. The study employs a holistic approach, addresses multiple dimensions of onboarding, and contributes to the theoretical research, perspectives from organizational psychology, management theory, multifaceted human resources practices and data analytics. The research methodology involves a combination of qualitative and quantitative research methods, conducting interviews with stakeholders and surveys of new hires. By examining onboarding processes, this study seeks to identify common patterns, challenges, and best practices. Key factors influencing onboarding process, such as administrative tasks, personalize onboarding experiences, employee engagement, and leveraging technology will be thoroughly examined. Focus will be given on interactive approach to combine all the elements together into a cohesive framework. The findings of this research aim to contribute valuable insights to both theoretical contributions and implications for human resources practices. Recommendations for optimizing new hire onboarding processes will be presented. Ultimately, the goal is to enhance the overall quality of onboarding process for new hires, incorporate technological solution, design personalized onboarding experiences, implement engagement strategies and evaluate the efficiency of the proposed framework through a pilot program.